Fracture behaviour, microstructure, and performance of various layered-structured Al2O3-TiC-WC-Co composites. Issue 14 (15th July 2021) - Liu, Changxia; Sun, Junlong; Wang, Chao; Li, Fengxun; Hussain, Tanvir
Abstract: In this study, layered-structured Al2 O3 -based composites containing WC-Co, TiC, and MgO additives were prepared using hot-pressing sintering. The best comprehensive mechanical characteristics were acquired for the sample with a layer number ( N LN ) of 7 and thickness ratio ( η TR ) of 6. Its composite exhibited a fracture toughness of 8.5 and 8.4 MPa m 1/2 in the X and Z directions, respectively. Analysis of the micro characteristics of the fracture surfaces of the Al2 O3 -TiC-WC-Co layered composites revealed a significant enhancement in the bending strength, which could be attributed to the mixed fracture modes in the composite, including intergranular and trans -granular modes. As the displacement increased, first, the bending stress of all the composites increased gradually, after which all the samples showed abrupt elevation in stress. The enhancement in the damage resistance of Al2 O3 -TiC-WC-Co layered composites could be attributed to the microscopic and macroscopic crack deflection, bridging, and partial surface bonding that occurred in the layers. Finally, a new theoretical perspective was employed to discuss the mechanism of the effect of the layered structure on the toughness of the composites.